Synthesis, Electro-optical Characteristic and Antimicrobial Efficacy of Some Benzothiazolium Asycyanine Colorants - Ansari, A.S.; Gupta, A.K. (Asian Journal of Chemistry, 2010)
Fourteen new benzothiazolium butadienylene chain substituted asycyanine colorants have been synthesised by catalytic condensation of two styryl pbenyl ketones namely 4-dimethylaminostyryl- 4´-nitrophenyl ketone and 4-dimethylaminostyryl-4´-methoxyphenyl ketone with 2-methyl benzothiazolium methiodide and 2-methyl-6-substituted benzothiazolium methiodides using piperidine as basic catalyst and ethanolic DMF as solvent. These colorants were synthesised with the object to study the effects of electron acceptor and donor substituents at the 4´-position in the chain β-phenyl nucleus, chain elongation, on visible absorption maxima and to evaluate their antimicrobial activity. The dyes were found to exhibit uniform increase of absorption maxima when collated with analogues having no substituents in the β-phenyl nucleus and the analogues having vinylene chain. Purified samples were also investigated in vitro against Staphylococcus aureus and E.fcherichia coli and some of them were found to be active.